Initial investigation of kinesiophobia as a predictor of functional reaction time one year after concussion - Melissa N Anderson; Robert C Lynall; Patrick J O’Connor; Julianne D Schmidt (Concussion, 2024)
Aim: The relationship between post-concussion kinesiophobia and clinical and functional reaction time (RT) beyond clinical recovery remains to be elucidated. Methods: College-aged participants with (n = 20) and without (n = 20) a concussion history completed patient-reported outcomes, and RT tasks. Kinesiophobia, symptoms and RTs were compared using t-tests. Linear regressions were performed to determine if kinesiophobia predicted RT measures and dual-task cost. Results: The concussion history group reported higher scores (p < 0.01) for all patient-reported outcomes. We observed significant single-task RT differences between groups (p = 0.013) such that those without a concussion history (m = 0.51s ± 0.08) were faster (m = 0.59s ± 0.12). There were no clinical or dual-task RT differences between groups (p > 0.05). Kinesiophobia significantly predicted single-task RT (R2 = 0.22). Discussion: Kinesiophobia should be considered when measuring RT.